Marine organic aerosol at Mace Head: effects from phytoplankton and source region variability - E. Chevassus; K. N. Fossum; D. Ceburnis; L. Lei; C. Lin; C. Lin; W. Xu; W. Xu; C. O'Dowd; J. Ovadnevaite (Atmospheric Chemistry and Physics)
Organic aerosol (OA) is recognized as a significant component of particulate matter (PM), yet their specific composition and sources, especially over remote areas, remain elusive due to the overall scarcity of high-resolution online data. In this study, positive matrix factorization was performed on organic aerosol mass spectra obtained from high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) measurements to resolve sources contributing to coastal PM. The focus was on a summertime period marked by enhanced biological productivity with prevailing pristine maritime conditions. Four OA factors were deconvolved by the source apportionment model. The analysis revealed primary marine organic aerosol (PMOA) as the predominant submicron OA at Mace Head during summertime, accounting for 42 % of the total resolved mass. This was trailed by more oxidized oxygenated organic aerosol (MO-OOA) at 32 %, methanesulfonic acid organic aerosol (MSA-OA) at 17 %, and locally emitted peat-derived organic aerosol (peat-OA) at 9 % of the total OA mass. Elemental ratios (O:C–H:C) were derived for each of these factors: PMOA (0.66–1.16), MO-OOA (0.78–1.39), MSA-OA (0.66–1.39), and peat-OA (0.43–1.34). The specific O:C–H:C range for MO-OOA hints at aliphatic and lignin-like compounds contributing to more oxidized organic aerosol formation. The total mass concentrations of primary organic aerosol and secondary organic aerosol were overall equal and almost exclusively present in the marine boundary layer, in agreement with previous findings. This study reveals that OA not only reflects atmospheric chemistry and meteorology – as evidenced by the significant ageing of summertime polar air masses over the North Atlantic, driven by ozonolysis under Greenland anticyclonic conditions – but also serves as an indicator of marine ecosystems. This is evident from MSA-OA being notably associated with stress enzyme markers and PMOA showing the typical makeup of largely abacterial phytoplankton extracellular metabolic processes. This study also reveals distinct source regions within the North Atlantic for OA factors. MSA-OA is primarily associated with the Iceland Basin, with rapid production following coccolithophore blooms (lag of 1–2 d), while diatoms contribute to a slower formation process (lag of 9 d), reflecting distinct oceanic biological processes. In contrast, PMOA is sourced from more variable ecoregions, including the southern Celtic Sea, western European Basin, and Newfoundland Basin, with additional contributions from chlorophytes and cyanobacteria at more southerly latitudes. Overall, these findings emphasize the need for longer-term investigations to further map the influence of phytoplankton taxa variability on aerosol composition and the broader impacts on aerosol–climate interactions.